Social Media Dynamics as A New Factor in African Politics - Czerep, Jędrzej (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
In the last years, the African political landscape has become increasingly influenced by the effects of the introduction of social media as a major channel for political debate. Apart from democratising the discourse, it has contributed massively to the spread of rumour, hate speech and disinformation, which had significant real-life effects on the ground.